Workplace Hazard Identification through Near-Miss Reports: A Social Network Analysis - Anggraini , Dita Putri; Ambarwati, Rita; Dedy, Dedy; Toirxonovna, Alimova Mashhura (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2024)
Occupational Safety and Health (OHS) is an effort to create a safe and healthy working environment. The company, which is engaged in power generation, experienced many near-miss cases from 2016 to 2023. Near-miss incidents are an early signal of the potential for severe accidents in the future if not resolved immediately. Identifying and addressing potential hazards early is necessary to prevent fatal work accidents. This study aims to analyze the reporting pattern of near-miss incidents by company employees through the IZAT application (Zero et al.) with a social network analysis (SNA) approach. This method identifies relationships and interaction patterns between employees in reporting near-miss incidents, thus revealing objects that need special attention. Data was obtained from September 2020 to July 2023. The analysis showed that 276 employees actively reported various near-miss incidents through IZAT (Zero Accident Assistant Application). This pattern reflects employees' sensitivity to potential hazards in their work environment. The findings of this study make a positive contribution to the improvement of the occupational safety and health management system in the company regarding the mitigation of potential hazards based on incoming report data. The recommendations provided are related to occupational safety aspects that need to be prioritized for management improvement. The implication of this research is to increase employee awareness in identifying and reporting potential hazards so as to prevent work accidents in the future.